Phenotypic and genotypic characterization of gardnerella vaginalis isolated from women with bacterial vaginosis from Hospital Kuala Lumpur, Malaysia - Younus Al-Assadi, Nada Khairi (2013)
Bacterial vaginosis (BV) is a highly prevalent, but poorly understood polymicrobial disorder of the human vaginal microbiota. Symptoms for BV include vaginal discharge, itching and odor. Gardnerella vaginalis which is commonly found in the vaginal mucosa of asymptomatic women is the frequent cause of BV. BV microbiota although dominated by G. vaginalis, it also includes a number of anaerobes. The main challenge in the diagnosis of BV is the identification of the correct etiological agents. Bacterial vaginosis if untreated leads to chronic infectious/inflammatory disease with multiple reproductive tract complications including preterm birth, neonatal infections and suppurative lesions. Treatment options as recommended by Center for Disease Control (CDC) include oral or intravaginal administration of metronidazole or clindamycin. Despite treatment with these antibiotics, treatment failure and recurrent infection rates are still rising. Therefore, this study is aimed at identifying methods for conclusive diagnosis of BV, and corrects laboratory techniques for isolation of G. vaginalis bacterium. Also this study is shed the light on determining the susceptibility of G. vaginalis strains against recommended antibiotics and determining the phenotypes and genotypes characteristics of this bacterium with its virulence properties. Two-hundred and seven vaginal swabs were collected from patients‟ attending the gynecological clinic at Hospital Kuala Lumpur (HKL), Malaysia from 16th February to 20th July 2012 and transported to the Medical Microbiology Laboratory, Universiti Putra Malaysia. One hundred and sixty (77.2%) out of 207 samples were recorded as symptomatic biased on clinical observation and due to the presence of vaginal discharge, while the remaining 47 (22.7%) were recorded as asymptomatic as they did not show any vaginal discharge. A patient is diagnosed for BV based on the Amsel-clinical criteria and Nugent-Gram staining. In the present study, comparison of Amsel-clinical criteria and Nugent-Gram stain in the diagnosis of BV showed the later to be more sensitive (91%) than the former (53%). Among the 160 samples, 47 (73.4%) were confirmed as G. vaginalis positive by phenotypic (culture, Gram stain and biochemical) and genotypic (16S rRNA) methods. Metronidazole (MTZ), which is a broad spectrum antibiotic against candidiasis and giardiasis is given as the first choice of drug for the treatment of BV. Among the studied 47 isolates, three showed resistance to MTZ and carried the nim gene which mediates MTZ resistance. A simple and reproducible scheme for identifying biotypes of G. vaginalis identified eight biotypes based on reaction for hippurate hydrolase, ONPG test and lipase test. Among the isolates studied, biotype 1 was the most prevalent (18/47 or 38%), followed by biotype 7 (17/47 or 36%), biotype 5 (8/47 or 17%), and finally biotype 8 (4/47 or 8.5%). Biotypes 2, 3, 4 and 6 were not observed. The biotypes did not show any significant association with the clinical reasons (abortion, minor surgery and vaginal fluid) for suspecting BV. Genotyping of the microbial pathogens is important in the management of infections as it gives useful information about the spread of pathogens. In addition, monitoring of endemic pathogens determines the adequacy of the general hygienic measures performed. All 47 G. vaginalis isolates when genotyped by amplified ribosomal DNA restriction analysis (ARDRA) produced three different genotypes (I, II and III). Similar to the biotypes, the genotypes also did not show any significant association with clinical data. Twelve (25%) isolates belonged to genotype I, 22 (46%) isolates to genotype II and 13 (27.6%) to genotype III. Isolates that were biotype 7 matched well with genotype II. G. vaginalis isolates when further screened for virulence factors, such as vaginolysin (vly, gene that mediate pore formation and cytotoxicity) and sialidase gene (mediate biofilm production), it was found that 25 (53%) and 26 (55%) carried sialidase and vly gene respectively. All G. vaginalis isolates of genotype I harbor the sialidase gene 12 (25.5%), and contain also vly gene 11 (23.4%). This result suggest of recording these strains as a virulent strains not as a commensally strains. In conclusion, characterization of G. vaginalis isolated from patients with BV revealed that for the accurate identification of G. vaginalis associated BV, combination of phenotypic and genotypic methods should be implemented in the routine diagnostic laboratory. As the G. vaginalis strains are highly diverse, susceptibilities towards recommended antibiotics are decreasing and frequently carry virulent and resistant genes, routine monitoring of the G. vaginalis important for the efficient management of bacterial vaginosis infection.